2005
DOI: 10.1002/ajp.20166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reproductive and social variables on fecal glucocorticoid levels in a sample of adult male ring‐tailed lemurs (Lemur catta) at the Beza Mahafaly Reserve, Madagascar

Abstract: Glucocorticoids, a group of adrenal hormones, are secreted in response to stress. In male primates, variables such as breeding seasonality, dominance hierarchy stability, and aggressive and affiliative interactions can affect glucocorticoid levels. In this study, we examined interindividual differences in mean fecal glucocorticoid (fGC) levels among males in three groups of wild ring-tailed lemurs to better understand the physiological costs of group living for males in a female-dominant species that exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 48 publications
(58 reference statements)
0
27
1
Order By: Relevance
“…However, we found no difference in fGC levels in lactating females when compared to non-lactating females at either site, nor did males and females differ in fGC levels across the study period, despite different reproductive challenges at different times of year. Studies on L. catta from other sites have been inconclusive with respect to the role of reproductive state on stress levels (Cavigelli, 1999;Gould et al, 2005). It may be that, barring other physiological challenges, reproductive demands fall within the Predictive Homeostatic range (Romero et al, 2009) and thus do not induce major GC fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found no difference in fGC levels in lactating females when compared to non-lactating females at either site, nor did males and females differ in fGC levels across the study period, despite different reproductive challenges at different times of year. Studies on L. catta from other sites have been inconclusive with respect to the role of reproductive state on stress levels (Cavigelli, 1999;Gould et al, 2005). It may be that, barring other physiological challenges, reproductive demands fall within the Predictive Homeostatic range (Romero et al, 2009) and thus do not induce major GC fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…GCs were extracted from fecal samples and measured via radioimmunoassay in accordance with procedures described elsewhere for L. catta (e.g. Cavigelli, 1999;Gould, Ziegler & Wittwer, 2005;Pride, 2005a,b,c;Starling et al, 2010; details in Supporting Information).…”
Section: Field Methodsmentioning
confidence: 99%
“…The majority of primate studies indicate that dominant males produce levels of GCs that are more than or equal to subordinate males, whereas only one study has found that subordinate males excrete more GCs than dominant males (table 1-see 'MALES-not inherited') [40,48,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. The opposite pattern emerges for females, where subordinate females often have greater GC production than dominant individuals, particularly when rank is not inherited rstb.royalsocietypublishing.org Phil.…”
Section: Sex Differences In Social Status and Glucocorticoid Productionmentioning
confidence: 99%
“…In mammals, on the other hand, the stress response is linked to an array of social traits, states and events that characterize individuals and their daily lives, a subset of these being reliable predictors of elevated GC levels. For example, behavioural traits such as aggression (Muller & Wrangham 2004), current states such as increased age (Sapolsky et al 1986) and reproductive status ( Fichtel et al 2007) and social context such as numbers of resident males (Gould et al 2005) and social instability (Brockman et al 2001) correlate with elevated GC responses. Likewise, demographic events such as male immigration (Alberts et al 1992), dispersal and specific events related to reproductive success such as mating (Strier et al 1999), birth of offspring (Berg & WynneEdwards 2001) and male infanticide (Engh et al 2006) have all been shown to be associated with elevated GC levels.…”
Section: Introductionmentioning
confidence: 99%